2022
DOI: 10.1038/s41422-022-00612-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel STING agonist-adjuvanted pan-sarbecovirus vaccine elicits potent and durable neutralizing antibody and T cell responses in mice, rabbits and NHPs

Abstract: The emergence of SARS-CoV-2 variants and potentially other highly pathogenic sarbecoviruses in the future highlights the need for pan-sarbecovirus vaccines. Here, we discovered a new STING agonist, CF501, and found that CF501-adjuvanted RBD-Fc vaccine (CF501/RBD-Fc) elicited significantly stronger neutralizing antibody (nAb) and T cell responses than Alum- and cGAMP-adjuvanted RBD-Fc in mice. Vaccination of rabbits and rhesus macaques (nonhuman primates, NHPs) with CF501/RBD-Fc elicited exceptionally potent nA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 96 publications
0
84
0
Order By: Relevance
“…Cells were re-fed in a fresh medium after 12 h. The luminescence detection was performed at 48 h post-infection. A luminescence value ten-fold higher than the untreated cell control was considered as positive [ 14 ]. TCID 50 was determined by using the Reed-Muench method.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were re-fed in a fresh medium after 12 h. The luminescence detection was performed at 48 h post-infection. A luminescence value ten-fold higher than the untreated cell control was considered as positive [ 14 ]. TCID 50 was determined by using the Reed-Muench method.…”
Section: Methodsmentioning
confidence: 99%
“…Generation of both pseudotyped wildtype SARS-CoV-2 and its Delta variant was performed as previously described [ 11 , 16 , 17 , 18 ]. Briefly, the backbone plasmid of pNL4-3.Luc.R-E- was co-transfected with the plasmid of pcDNA3.1-SARS-CoV-2-S (D614G)/pcDNA3.1-SARS-CoV-2-S (Delta) into HEK-293T cells by using VigoFect transfection reagent (Vigorous Biotechnology, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of nAbs against pseudotyped SARS-CoV-2 and its Delta variant was conducted as previously described [ 11 , 19 ]. Briefly, the mouse sera from all 12 groups were inactivated at 56 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Liu et al 7 compared STING agonists with several well-known adjuvants, such as Alum and cGAMP. They found that the STING agonist CF501-adjuvanted RBD-Fc vaccine (CF501/RBD-Fc) elicited significantly stronger nAb and T cell responses than Alum- and cGAMP-adjuvanted RBD-Fc vaccine in mice.…”
mentioning
confidence: 99%